„Le mur du langage” – samotność według Jacques’a Lacana (inność, porozumienie, miłość) - Choińska, Bogna (Wydawnictwo Naukowe UAM, 2011)
In my article I discuss the concept of the subject from the Lacanian psychoanalysis point of view. My aim is to show that the subject seen from such a perspective is condemned to total loneliness. I refer to three different points: otherness, comprehension and love. In Lacan’s psychoanalysis the difference is referred to as the Real (subject as je). The Real is in opposition to the Symbolic and Imaginary (subject as moi). Therefore, the world, other people and oneself can be understood as absolutely different. Taking such a definition of the otherness, the comprehension is impossible, because it takes place within symbolic sphere, which is false and alien to the subject (je). The otherness and inability of understanding determine treating love as transferred and always directed to imaginary subject. What is important, the theory of the subject as homo symbolicus, even though seemingly in agreement with anti-positivist theory, does not allow to cross lingual and to direct approaching to the otherness. The otherness may be deciphered only within the Imaginary as a disturbance within it, as a temporary lack of sense.
„Le mur du langage” – loneliness according to Jacques Lacan (otherness, comprehension, love)